Higher involvement of synergistic muscle than active muscles in ankle plantar flexion - Ying Xu; Jinping Li; Xiaowen Ju; Ying Hou (Scientific Reports)
Abstract The aim of this study was to observe the activation characteristics of calf muscles in healthy adults during plantar flexion by a new nonlinear electromyography index. The linear indices of sEMG, including the root mean square (RMS), median frequency (MF), and nonlinear index, degree centrality (DC) of the calf muscles of ten healthy male participants, were tested in the resting state and plantar flexion position to analyse their characteristics. The RMS was not normally distributed, and the MF and DC values were normally distributed. Compared with those in the resting state, the RMS, MF and DC values of all the tested muscles were significantly greater (P < 0.05) during plantar flexion. Among all the muscles, the peroneus longus (PL) changed the most. The RMS increased from 3.14 ± 1.61 µV to 49.31 ± 21.81 µV, the MF increased from 134.07 ± 30.86 Hz to 203.55 ± 28.36 Hz, and the DC changed from 2.24 ± 0.38 to 3.33 ± 0.41. Two linear indices and a nonlinear index of the PL were significantly elevated during prone plantar flexion. We speculate that the nonlinear index, DC can reflect the degree of single muscle synergistic involvement, and may become a new indicator for assessing the state of single muscle controlled by nervous system in a movement involving multiple muscles.